FASTRACK II magnetic resonance imaging sub-study Diffusion and perfusion biomarkers for renal SABR response. (October 2020) - Korte, J C; Reynolds, H; Lasocki, A; Vanneste, B G L; Miclea, R; Backes, W H; Sridharan, S; Sidhom, M; Rai, R; Kron, T; Hardcastle, N; Siva, S
Abstract: Stereotactic ablative body radiotherapy (SABR) is demonstrating good local control for patients with inoperable primary renal cell carcinoma. In a previous pilot study we identified magnetic resonance imaging (MRI) early response biomarkers that correlate with later morphological changes in computed tomography (CT) images. These early functional changes in diffusion and perfusion following radiotherapy were observed on MRI and have the potential to identify non-responders who may benefit from adjuvant or salvage therapies. Here we detail the imaging protocol for an MRI sub-study of the Focal Ablative STereotactic Radiosurgery for Cancers of the Kidney (FASTRACK II) trial. A preliminary patient case demonstrates the high quality of the imaging data, with discussion of the improvements made from the pilot protocol for improved motion management and correction. We aim to validate the previously identified early response MRI biomarkers with this rich prospective multi-centre dataset.